Nanoparticle–polymer interfacial layer properties tune fragility and dynamic heterogeneity of athermal polymer nanocomposite films. Issue 43 (25th October 2018) - Begam, Nafisa; Das A, Nimmi; Chandran, Sivasurender; Ibrahim, Mohd; Padmanabhan, Venkat; Sprung, Michael; Basu, J. K.
Abstract : Enthalpic interactions at the interface between nanoparticles and matrix polymers are known to influence various properties of the resultant polymer nanocomposites (PNC). Abstract : Enthalpic interactions at the interface between nanoparticles and matrix polymers are known to influence various properties of the resultant polymer nanocomposites (PNC). For athermal PNCs, consisting of grafted nanoparticles embedded in chemically identical polymers, the role and extent of the interface layer (IL) interactions in determining the properties of the nanocomposites are not very clear. Here, we demonstrate the influence of the interfacial layer dynamics on the fragility and dynamical heterogeneity (DH) of athermal and glassy PNCs. The IL properties are altered by changing the grafted to matrix polymer size ratio, f, which in turn changes the extent of matrix chain penetration into the grafted layer, λ . The fragility of PNCs is found to increase monotonically with increasing entropic compatibility, characterised by increasing λ . Contrary to observations in most polymers and glass formers, we observe an anti-correlation between the dependence on IL dynamics of fragility and DH, quantified by the experimentally estimated Kohlrausch–Watts–Williams parameter and the non-Gaussian parameter obtained from simulations.